2014
DOI: 10.3109/09537104.2014.881991
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma (PRP): Methodological aspects and clinical applications

Abstract: The clinical use of platelet-rich plasma (PRP) is based on the increase in the concentration of growth factors and in the secretion of proteins which are able to maximize the healing process at the cellular level. Since PRP is an autologous biologic material, it involves a minimum risk of immune reactions and transmission of infectious and contagious diseases, and it has been widely used for the recovery of musculoskeletal lesions. Despite the great potential for applicability, the implementation of the therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
111
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(129 citation statements)
references
References 101 publications
1
111
0
5
Order By: Relevance
“…In a previous study [1], we reported that the optimal speed for centrifugation was 2400 rpm (950g) 9 10 min and 3600 rpm (2200g) 9 15 min for the first and second spin, respectively. Importantly, it should be noted that although collecting platelets is faster and more efficient, faster centrifugation speeds beyond an optimum level may over-activate platelets and result in the release and diffusion of growth factors into other fractions [37]. Optimization of these conditions has been considered in automated PRP preparation systems; when choosing manual preparation, individual clinical operators should determine optimal conditions based on the recovery of key growth factors.…”
Section: Automated Preparationmentioning
confidence: 98%
See 1 more Smart Citation
“…In a previous study [1], we reported that the optimal speed for centrifugation was 2400 rpm (950g) 9 10 min and 3600 rpm (2200g) 9 15 min for the first and second spin, respectively. Importantly, it should be noted that although collecting platelets is faster and more efficient, faster centrifugation speeds beyond an optimum level may over-activate platelets and result in the release and diffusion of growth factors into other fractions [37]. Optimization of these conditions has been considered in automated PRP preparation systems; when choosing manual preparation, individual clinical operators should determine optimal conditions based on the recovery of key growth factors.…”
Section: Automated Preparationmentioning
confidence: 98%
“…However, if on-site preparation and immediate use of allogeneic PRP is pursued, well-trained operators and clinicians should perform the preparation and quality control of PRP preparations according to guidelines or standardized protocols for both medical and economic reasons. Such protocols are not yet standardized internationally, but individual research groups have recently proposed various standardized protocols for the preparation of autologous PRP [6,28,37]. Additionally, the International Cellular Medical Society has released guidelines for the use of PRP [67].…”
Section: Recipient Factors That Influence Clinical Outcomes Of Platelmentioning
confidence: 99%
“…Merques et al [6] devised a simple method similar to ours. By the way, our method could use PRP preparation in step 1.…”
Section: Discussionmentioning
confidence: 99%
“…Os ativadores mais comumente utilizados são a trombina (bovina ou autóloga), colágeno tipo I, cloreto e gluconato de cálcio a 10% (CASTILLO et al, 2010;DELONG;RUSSELL;MAZZOCCA, 2012;MARQUES et al, 2015;SCARANTO, 2002). Em função do tipo e concentração do ativador, o PRP pode adquirir a forma de gel, coágulo ou líquido, sendo este último quando são empregadas pequenas concentrações de sais de cálcio, ou quando o PRP é aplicado sem ser ativado, para que as plaquetas sejam degranuladas mais lentamente e de forma endógena (DELONG; RUSSELL; MAZZOCCA, 2012).…”
Section: Plasma Rico Em Plaquetas (Prp)unclassified
“…Apesar da extensa variação metodológica, diante do benefício funcional associado às plaquetas, o PRP tem sido utilizado com sucesso em diversas áreas cirúrgicas com o propósito do reparo tecidual, em especial na regeneração óssea e no controle de feridas crônicas de difícil cicatrização (ANITUA et al, 2008;ANITUA;TROYA;ORIVE, 2013;KAZAKOS et al, 2009;MARQUES et al, 2015;MARX, 2004;YANG et al, 2011).…”
Section: Plasma Rico Em Plaquetas (Prp)unclassified